2011
DOI: 10.1007/s10549-011-1854-y
|View full text |Cite
|
Sign up to set email alerts
|

Local treatment of mixed osteolytic/osteoblastic spinal metastases: is photodynamic therapy effective?

Abstract: The widespread use of systemic and local therapies aimed at spinal metastatic lesions secondary to breast cancer has increased the incidence of mixed osteolytic/osteoblastic patterns of bony disease. The complex structure of these lesions requires novel therapeutic approaches to both reduce tumor burden and restore structural stability. In photodynamic therapy (PDT), a minimally invasive approach can be used to employ light to activate a photosensitizing agent that preferentially accumulates in tumor tissue, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…While BPs are known to inhibit and induce apoptosis in osteoclasts, the osteoclasts may return to physiologically normal levels 7 weeks after a BP single injection. Similarly, it has been shown that PDT decreases osteoclast activity, particularly in metastatically‐involved vertebrae observed at 1 week post‐PDT treatment . However, local PDT likely would not continue to affect osteoclast proliferation/presence 6 weeks post‐PDT treatment, resulting in the restoration of physiologically normal levels of osteoclasts as seen in this study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While BPs are known to inhibit and induce apoptosis in osteoclasts, the osteoclasts may return to physiologically normal levels 7 weeks after a BP single injection. Similarly, it has been shown that PDT decreases osteoclast activity, particularly in metastatically‐involved vertebrae observed at 1 week post‐PDT treatment . However, local PDT likely would not continue to affect osteoclast proliferation/presence 6 weeks post‐PDT treatment, resulting in the restoration of physiologically normal levels of osteoclasts as seen in this study.…”
Section: Discussionsupporting
confidence: 63%
“…In Wistar rats, trends towards enhancement in both bone architecture and strength were found 1 week after PDT, with significant improvement 6 weeks post‐treatment . Further study in young athymic rats, a model necessary for the establishment of skeletal metastasis, demonstrated benefits of PDT in osteolytic and mixed osteolytic/osteoblastic vertebral metastases . Combined treatment of BP with PDT had an even more profound effect on enhancing bone structure and strength in osteolytic vertebrae, at one week post‐treatment .…”
mentioning
confidence: 87%
“…In this work, we explored the potential of phosphonate-functionalized NaGdF 4 :Yb,Er UCNPs to behave as MRI and PET imaging tools for bones, motivated by the long-term prospect of designing theranostic nanoconstructs for the photoactivated delivery of metal-based drugs. Actually, recent results highlight the possibility of adopting photodynamic therapy and related strategies for the treatment of spinal metastases [11] and to ablate tumors within vertebral bone [12]. Therefore, phosphonate ligands were selected for functionalization of UCNPs because of their capacity of accumulating in bones.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence from animal models has shown that light travels within tumour-involved bone with minimal obstruction from the surrounding cortical bone. In fact, non-involved cortical bone may act as a barrier to prevent light travelling to the spinal cord [11][12][13][14][15][16][17][18][19] . • Delivery of light to the target tissue:°…”
Section: Challenges • Light Transmission Through Bone:°mentioning
confidence: 99%